Half a Century of Work–Nonwork Interface Research: A Review and Taxonomy of Terminologies. Issue 3 (21st October 2018) - Beigi, Mina; Shirmohammadi, Melika; Otaye‐Ebede, Lilian
Abstract : The extensive interest in the work‐nonwork interface over the years has allowed scholars from multiple disciplines to contribute to this literature and to shed light on how professional and personal lives are related. In this paper, we have identified 48 terminologies that describe the interface or relationship between work and nonwork, and have organised them into mature, intermediate, and immature categories according to their stage of development and theoretical grounding. We also provide a taxonomy that places work‐nonwork interface terminologies into a matrix of six cells based on two dimensions: (1) type of nonwork being narrow or broad; and (2) nature of the mutual impact of work and nonwork domains on one another, characterising the impact as negative, positive, or balanced. The type of nonwork dimension was informed by Frone's (2003) classification of employees' lives into multiple subdomains; the mutual impact dimension was informed by frameworks that organised the literature in part by negative, positive, and balanced work‐nonwork interface constructs (e.g., Allen, 2012; Greenhaus & Allen, 2011). Theoretical contributions of the proposed taxonomy are discussed along with suggestions on important avenues for future research.